Large Individual Differences in Serum 25-Hydroxyvitamin D Response to Vitamin D Supplementation: Effects of Genetic Factors, Body Mass Index, and Baseline Concentration. Results from a Randomized Controlled Trial - Sollid, S. T.; Hutchinson, M.Y. S.; Fuskevåg, O. M.; Joakimsen, R. M.; Jorde, R. (Hormone and Metabolic Research, 2016)
The main aim of the study was to determine the influence of genetic factors on the serum 25-hydroxyvitamin D response to vitamin D supplementation. The main outcome measure was an increase in serum 25-hydroxyvitamin D after vitamin D supplementation. The patients are part of a randomized controlled trial in individuals with prediabetes assigned to 20 000 IU of vitamin D3 per week or placebo for 12 months. A total of 484 subjects were included in the analyses and genotyped for single nucleotide polymorphisms in the DBP, DHCR7, CYP2R1, and CYP24A1 genes. Single nucleotide polymorphisms from all 4 selected genes were significantly related to baseline serum 25-hydroxyvitamin D concentrations with differences between major and minor homozygote genotypes ranging from 4.4 to 19.2 nmol/l. In the subjects given vitamin D, those with genotypes with the highest baseline 25-hydroxyvitamin D concentration also had the highest 25-hydroxyvitamin D concentration after 12 months, and the increase (delta) in 25-hydroxyvitamin D was significantly related to 3 of the single nucleotide polymorphisms. The increase in serum 25-hydroxyvitamin D was also higher in lean vs. obese subjects, and higher in those with low baseline 25-hydroxyvitamin D concentrations. When combining these 3 factors in a linear regression model, the predicted (and observed) difference in 25-hydroxyvitamin D increase between high and low responders to the supplementation was approximately 60 nmol/l. In conclusion, due to genetic, body mass, and baseline 25-hydroxyvitamin D differences, there are huge individual variations in the serum 25-hydroxyvitamin D response to vitamin D supplementation that could be of clinical importance.
Keywords: serum 25-hydroxyvitamin D; vitamin D supplementation; genetic factors